. Analysis of Teacher Skills in Reinforcement Students Using Myer Briggs Type Indicator (MBTI) at The Seventh Grade of UPTD SMPN 4 Gunungsitoli in 2024/2025: English - Reyza Cut Nanda Zalukhu; Hidayati Daeli; Yasminar A. Telaumbanua; Afore T. Harefa (Journal of English Development, 2025)
This study explores the relationship between teachers’ reinforcement skills and Myers-Briggs Type Indicator (MBTI) personality types. The study examines how teachers can utilize the 16 MBTI personality types (e.g., INTJ, ENTP, ISFJ, ESFP) to support students in the classroom. The shift to Independent Curriculum, aimed at improving educational standards, presents new challenges and opportunities, particularly in English language teaching. Observations at UPTD SMPN 4 Gunungsitoli highlighted the need for creative reinforcement skills for 31 seventh-grade students in their developmental stages. Using a descriptive qualitative methodology, data were collected through observations and interviews with English teachers to determine students’ MBTI profiles and analyze their reinforcement needs. Findings suggest that MBTI-based reinforcement, whether verbal, nonverbal, positive, or negative, can positively influence students’ personality and learning processes. The study concludes that MBTI can serve as a valuable tool for educators in tailoring reinforcement strategies to foster students’ character development and deeper learning.